2019
DOI: 10.1111/1348-0421.12716
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence and characterization of virulence genes in Lancefield group C Streptococcus dysgalactiae isolated from farmed amberjack (Seriola dumerili)

Abstract: Lancefield group C Streptococcus dysgalactiae causes infections in farmed fish. Here, the genome of S. dysgalactiae strain kdys0611, isolated from farmed amberjack (Seriola dumerili) was sequenced. The complete genome sequence of kdys0611 consists of a single chromosome and five plasmids. The chromosome is 2,142,780 bp long and has a GC content of 40%. It possesses 2061 coding sequences and 67 tRNA and 6 rRNA operons. One clustered regularly interspaced short palindromic repeat, 125 insertion sequences, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Recently, Nishiki et al 7 sequenced the first SD isolate from fish, and reported a closer resemblance to SDSD than SDSE. However, their result was influenced by the inclusion S. equi in the phylogenetic analysis, reducing the basis of the comparison to 126 core genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Nishiki et al 7 sequenced the first SD isolate from fish, and reported a closer resemblance to SDSD than SDSE. However, their result was influenced by the inclusion S. equi in the phylogenetic analysis, reducing the basis of the comparison to 126 core genes.…”
Section: Discussionmentioning
confidence: 99%
“…Rosinski-Chupin et al 27 revealed a reductive evolution to be the most notable in fish-adapted S. agalactiae variants, primarily comprising deletion and inactivation of several metabolic functions. In piscine SD isolates, disruption of the emm -gene operon and pilus island1 by insertion sequences has been reported 7 . Similarly, we observed insertion sequences affecting other virulence factors in SD, including the deletion of the emm -gene in most swine associated SD isolates and the Streptolysin S operon in all SDSD isolates (Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study also described moderate‐to‐severe non‐purulent encephalomyelitis in infected fish. The complete genome sequence and characterization of virulence genes of S. dysgalactiae isolated from farmed greater amberjack were recently described (Nishiki et al, 2019). A possible misdetection problem could occur with L. garvieae , which exhibits clinical similarities (Nomoto et al, 2004).…”
Section: Bacteriamentioning
confidence: 99%
“…Recently, the whole‐genome sequence of GCSD strain (kdys061) isolated from farmed amberjack ( Seriola dumerili ) was reported (Nishiki, Yoshida, & Fujiwara, 2019). The complete genome sequence consists of a single chromosome and five plasmids.…”
Section: Characterization and Identificationmentioning
confidence: 99%